2020
DOI: 10.1177/2378023120964376
|View full text |Cite
|
Sign up to set email alerts
|

“Dad, Wash Your Hands”: Gender, Care Work, and Attitudes toward Risk during the COVID-19 Pandemic

Abstract: Recent analyses of responses to coronavirus disease 2019 (COVID-19) have posited that men’s dismissive attitudes toward the risks of the virus reflect their attempts to conform to masculine norms that valorize bravery and strength. In this article, the authors develop an alternative account of the gender differences in attitudes toward COVID-19. Drawing on three waves of in-depth interviews with college students and members of their households ( n = 45) over a period of 16 weeks (for a total of 120 interviews)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…Sobo and colleagues (2016), these findings highlight the consequences of our consumeristic, individualistic medical system, and they help to clarify and quantify the gendered impact of that system on women and mothers. As family health managers, mothers actively work to control their children's exposure to health risks (Burton-Jeangros 2011; Estep and Greenberg 2020;Mackendrick 2014;Reich 2014Reich , 2016bReich , 2016aReich , 2020bReich , 2020aSobo et al 2016;Umamaheswar and Tan 2020;Waggoner 2017). In the context of politicized misinformation about COVID-19 (Loomba et al 2001), some mothers perceive themselves as more able to control their children's risks of severe complications from the virus than their children's perceived risks of side effects from the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sobo and colleagues (2016), these findings highlight the consequences of our consumeristic, individualistic medical system, and they help to clarify and quantify the gendered impact of that system on women and mothers. As family health managers, mothers actively work to control their children's exposure to health risks (Burton-Jeangros 2011; Estep and Greenberg 2020;Mackendrick 2014;Reich 2014Reich , 2016bReich , 2016aReich , 2020bReich , 2020aSobo et al 2016;Umamaheswar and Tan 2020;Waggoner 2017). In the context of politicized misinformation about COVID-19 (Loomba et al 2001), some mothers perceive themselves as more able to control their children's risks of severe complications from the virus than their children's perceived risks of side effects from the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Under an individualistic and consumeristic medical model, people are expected to take responsibility for their health and avoid health risks (Clarke et al 2003;Estep and Greenberg 2020;Reich 2020a;Timmermans and Oh 2010). In this system, mothers and women who may become mothers face particularly strong pressures to control risks to their families' health (Burton-Jeangros 2011;Elliott and Bowen 2018;Gage-Bouchard 2017b;Mackendrick 2014;Ranji and Salganicoff 2014;Reich 2014Reich , 2020aUmamaheswar and Janani 2020;Waggoner 2017). As a result, women generally report greater concerns about risks than men (Borghans et al 2009;Rosen, Tsai, and Downs 2003) and are also more likely than men to follow expert medical recommendations (Courtenay 2000;Courtenay, Mccreary, and Merighi 2002;Denton and Walters 1999;Read and Gorman 2010;Umamaheswar and Janani 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This too has to do with the social and cultural constructions of gender. For instance, Janani Umamaheswar and Catherine Tan’s (2020) longitudinal study with college students in the United States found that men in their sample were more likely than women to downplay the risks associated with COVID-19. Yet they also found that men with significant caregiving responsibilities expressed similar levels of fear and concern to women in their sample.…”
mentioning
confidence: 99%